FAKTOR -FAKTOR FINANCIAL DISTRESS TERDAPAT PADA PERUSAHAAN MANUFAKTUR TERDAFTAR BEI 2020-2021 - Nugroho, Totok Susilo Pamuji (STIE Atma Bhakti, 2024)
This study tests the factors that influence financial distress in manufacturing companies listed on the IDX (Indonesia Stock Exchange) in 2020-2021. There are several factors tested, including: liquidity, leverage and sales growth. This type of research is quantitative. The population used is manufacturing companies listed on the IDX . This study uses a purposive sampling method to test samples and 37 manufacturing companies were obtained. Data analysis uses multiple linear regression using the SPSS 26.0 program. The results of this study indicate that the partial hypothesis calculation of the liquidity variable has no significant effect. The leverage variable has a significant negative effect, and sales growth has a significant positive effect on financial distress. The results of this study also obtained the Determination Coefficient (R2) with a value of 0.762, meaning that 76.2% of disclosure is explained by variables between liquidity, leverage, and sales growth, while the remaining 23.8% is explained by other variables outside the model.